Beyond privatization: bureaucratization and the spatialities of immigration detention expansion. Issue 3 (3rd July 2017) - Hiemstra, Nancy; Conlon, Deirdre
ABSTRACT: Beyond privatization: bureaucratization and the spatialities of immigration detention expansion. Territory, Politics, Governance . Immigration detention has become central to models of immigration enforcement in the United States and globally. This paper elaborates a conceptual framework to facilitate critical understanding of detention's proliferation that goes beyond the role of privatization as well as beyond public–private sector relationships. It draws on a study of immigration detention in Essex County, New Jersey, with a focus on the contractual arrangements delineating detention between public and private entities and actors. Our conceptual framework posits processes of bureaucratization as central to the growth in immigration detention. We understand bureaucratization as a spatialized process of obfuscation that both builds multidimensional webs of interdependence between public and private actors and flattens these relationships into one-dimensional rational economic decisions and exchanges. Through this framework, we see contractual agreements that are remarkable for fostering overlapping, snowballing relationships in the operation of facilities, while they simultaneously conceal powerful influences behind detention's expansion, mask human rights abuses of detained migrants, and filter out moral concerns from decision-making regarding detention.